A Study on Comparative Analysis of Dry Cupping and Dry Needling for Shoulder Tendinitis in Weightlifters - Riya Gulati; Dr. Vaishali Chaudhary; Dr. Monika Sharma (Revista Electronica de Veterinaria, 2024)
Introduction: Shoulder tendinitis is a common musculoskeletal condition among weightlifters, characterized by Inflammation and degeneration of the shoulder tendons due to repetitive overhead movements.Effective treatment options are necessary to reduce pain and restore function. Dry needling (DN) and dry cupping (DC) are two commonly used techniques for managing musculoskeletal pain, but their comparative effectiveness in treating shoulder tendinitis remains underexplored.Aim and Objectives: The primary aim of this study is to compare the effectiveness of dry cupping and dry needling in the management of shoulder tendinitis in weightlifters. Specifically, the study seeks to assess and compare pain relief and functional improvement achieved through dry cupping and dry needling, using validated assessment tools such as the Shoulder Pain and Disability Index (SPADI) and the Numerical Rating Scale (NRS).Methodology: A comparative study was conducted on 30 weightlifters diagnosed with shoulder tendinitis. Participants were randomly assigned to two groups: Dry Needling (DN) Group and Dry Cupping (DC) Group. Pain levels were measured using the Numerical Pain Rating Scale (NPRS) and functional outcome using Shoulder pain and Disability Index (SPADI) before and after treatment. Functional assessments and range of motion (ROM) evaluations were also conducted. Statistical analyses, including paired and independent t-tests, were performed to determine the effectiveness of each intervention.Results: Both Dry Needling and Dry Cupping proved to be effective interventions for reducing shoulder pain and disability, as evidenced by the statistically significant reductions in NPRS and SPADI scores. However, Dry Needling demonstrated superior results in both pain reduction and functional improvement, as indicated by the greater mean score reductions and stronger t-test values.Discussion: Findings suggest that the Dry needling is more effective in treating shoulder tendinitis. However Dry cupping with various modern other techniques may provide superior outcomes. Further research is needed to explore the integration of multiple rehabilitation strategies.Conclusion: Dry needling was found to be more effective than dry cupping in reducing pain and improving shoulder function in weightlifters with shoulder tendinitis. These findings suggest that DN may be the preferred intervention for this condition. Further research with larger sample sizes and longer follow-up periods is recommended to confirm these results.